LEADERSHIP, WORK DISCIPLINE, AND WORK MOTIVATION AS DETERMINANTS OF JOB SATISFACTION AMONG EMPLOYEES AT THE YOUTH AND SPORTS AGENCY OF SOUTH SUMATRA PROVINCE - Fitriani; Juhaini Alie (Magister Manajemen Universitas Islam Malang, 2024)
This study aims to analyze the influence of leadership, work discipline, and work motivation on employee job satisfaction at the Youth and Sports Office of South Sumatra Province. The independent variables in this study are leadership (X1), work discipline (X2), and work motivation (X3), while the dependent variable is job satisfaction (Y). This study employed a quantitative approach with a survey method. The population consisted of 100 employees at the Youth and Sports Office of South Sumatra Province, all of whom were included as the sample using a saturated sampling technique. Data were analyzed using classical assumption tests, multiple linear regression analysis, F-test, t-test, and coefficient of determination at a 5% significance level. The results indicate that leadership, work discipline, and work motivation simultaneously and partially have a positive and significant effect on employee job satisfaction. This research provides a theoretical contribution to the development of human resource management science, especially in understanding the factors that affect job satisfaction. The practical implication of the study is the need to improve leadership effectiveness, enforce discipline, and strengthen work motivation to create a more productive and conducive work environment in the public sector.